A robust photocatalyst of Au25@ZIF-8@TiO2-ReP with dual photoreductive sites to promote photoelectron utilization in H2O splitting to H2 and CO2 reduction to CO. Issue 86 (11th October 2019) - Tian, Linyuan; Luo, Yucheng; Chu, Kunlin; Wu, Dongjun; Shi, Jianying; Liang, Zhenxing
Abstract : Heterogenization of double redox active sites Au25 NCs and a Re(i ) complex via composition engineering with improvement of activity and stability. Abstract : Sustaining long-term chemical or photochemical stability of a homogeneous molecular catalyst remains a significant challenge. We report a remarkable improvement of the activity and stability of a Au25 @ZIF-8@TiO2 -ReP catalyst via composition engineering with double redox active sites of Au25 NCs and a Re(i ) complex for H2 and CO evolution to promote electron utilization.